he standard form of a quadratic efunctionis:
![\begin{gathered} y=ax^2+bx+c \\ \text{Where } \\ a,b,\text{ and }c\text{ are real constants such that }a\\e0. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vcvgqxwnxu2j01sa9qu1fwrc03yrypvh9s.png)
Since the y-intercept is (0, -1.4), it follows that:
![\begin{gathered} -1.4=a(0)^2+b(0)+c \\ \text{ Therefore,} \\ c=-1.4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wyk4qo9g0f3l41g10r5kyrf8yggcfz0x3l.png)
Substitute c = -1.4 into the equation:
![y=ax^2+bx-1.4](https://img.qammunity.org/2023/formulas/mathematics/college/rmww7a8l4b2brovjsk1nk0sk18ouns2tyd.png)
Since the x-intercept is (0.905, 0), it follows that:
![\begin{gathered} a(0.905)^2+b(0.905)-1.4=0 \\ \text{Therefore,} \\ 0.819025a+0.905b=1.4-------(1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z60tjc0n6kdw9wjba0klq0t1npsbqr8rhp.png)
Since the graph passes through the third point (2, 0.6), it follows that:
![\begin{gathered} 0.6=a(2)^2+b(2)-1.4 \\ \text{Therefore} \\ 4a+2b-1.4=0.6 \\ 4a+2b=0.6+1.4_{} \\ 4a+2b=2 \\ \text{Divide both sides by }2 \\ 2a+b=1 \\ \text{Hence} \\ b=1-2a---------(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9tl9i3b4ctz2zqwcmyow1ln5u9306rrb9f.png)
Substitute equation (2) into equation (1):
![\begin{gathered} 0.819025a+0.905(1-2a)=1.4 \\ 0.819025a+0.905-1.81a=1.4 \\ \text{ Collect like terms:} \\ 0.819025a-1.81a=1.4-0.905 \\ -0.990975a=0.495 \\ \text{ Therefore,} \\ a=(0.495)/(-0.990975) \\ a\approx-0.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cwr6u7i91y9dx75c62usdmr20xxy46i4dc.png)
Substitute a = -0.5 into equation (2), therefore,
![b=1-2(-0.5)=1+1=2](https://img.qammunity.org/2023/formulas/mathematics/college/zkd3ey8b1ccct5cfijzm96iy9jlvnlym83.png)
Therfore the function is given by:
![y=-0.5x^2+2x-1.4](https://img.qammunity.org/2023/formulas/mathematics/college/yycgofedz2n1330vzlqsab78ckizz3bg41.png)
The equation of the parabola is y = -0.5x² + 2x - 1.4
.